HUBUNGAN PENDIDIKAN ANAK USIA DINI NON FORMAL DENGAN PERKEMBANGAN ANAK DI KECAMATAN GATAK KABUPATEN SUKOHARJO - Putriarsih, Ryanawati; Parwatiningsih, Sri Anggarini; Mulyani, Sri (Universitas Pesantren Tinggi Darul Ulum, 2017)
ABSTRACT Background: The effective early age children education is very useful to construct the structure of children development. The objective of the research is find out the correlation between non formal early age children education with children development.Research Method: Analytic observational method with cross sectional approach. Sample are 1-4 years old children in Ngemplak Village Gatak Subdistrict Sukoharjo Regency using proportional random sampling technique. Data collection with direct interview and DDST test. The research is analyzed by using chi square and contingency coefficient test to find out the correlation rate.Result: The whole children who attend the non formal early age children education have normal development (100%) and children who did not attend non formal early age education have suspect development (62.5%) and normal development (37.5%). The significant score of chi square test is p=0.000 and contingency coefficient score is 0.542.Conclusion: The conclusion of the research indicated that there is significant correlation between the non formal early age children education with children development. Keywords: The Non formal Early Age Children Education, Children Development, DDST